2000
DOI: 10.1002/(sici)1097-0223(200002)20:2<163::aid-pd769>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of abdominal enteric duplications

Abstract: Alimentary tract duplications are rare congenital malformations with few reports of the antenatal sonographic appearance. Early diagnosis is of paramount importance to prevent complications. We present a case of a cystic gastric duplication diagnosed antenatally at 31 weeks' gestation, which was treated successfully. Simultaneously, we review all published cases of prenatally diagnosed enteric duplications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 11 publications
0
15
0
1
Order By: Relevance
“…6,8,14 Our experience indicates that early intervention will be necessary for those patients who become symptomatic and that it is probably safe to watch the duplication until the asymptomatic child is older, at which point, elective surgery technically is easier. The finding of an intraabdominal cyst antenatally also may have implications for the obstetric management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,8,14 Our experience indicates that early intervention will be necessary for those patients who become symptomatic and that it is probably safe to watch the duplication until the asymptomatic child is older, at which point, elective surgery technically is easier. The finding of an intraabdominal cyst antenatally also may have implications for the obstetric management.…”
Section: Discussionmentioning
confidence: 99%
“…Features of an antenatally detected abdominal cyst making the diagnosis of an enteric duplication cyst more likely include presence on second trimester scan, because ovarian cysts are frequently not present until the third trimester; 15,16 a thick, multilayered echogenic wall, which is extremely suggestive; 14,19 and peristalsis in the cyst wall. 4, 12 Surgery, early in the series, consisted of a laparotomy and removal of the affected ileal segment, plus or minus the ileocecal junction and the appendix with an end-to-end ileo-ileal or ileocecal anastomosis.…”
Section: Methodsmentioning
confidence: 99%
“…Our case underwent surgery 9 days after birth without any complications. Correia-Pinto et al [12] reviewed 14 cases of abdominal enteric duplications found prenatally although none had IDC as in our patient. Nine of these 14 had surgical treatment during neonatal period and outcome was uneventful in all infants.…”
Section: Discussionmentioning
confidence: 99%
“…Twin Fetus Diagnosis and management *Shahila Sheik, 1 Mariam Mathew, 1 Mohamed Abdellatif, 2 Asim Qureshi, 3 Prakash Mandhan 4 online case report E nteric duplication cysts are rare congenital anomalies that occur anywhere in the gastrointestinal tract, with a greater predilection towards the ileal region. 1,2 The reported incidence is 1:4,500 newborns, and the embryogenesis of these anomalies remains controversial.…”
Section: Multiple Enteric Duplication Cysts In Amentioning
confidence: 99%
“…3 We report a case of an antenatally diagnosed enteric duplication cyst in one of a set of twins which was managed successfully after birth. A literature review is also included.…”
Section: Multiple Enteric Duplication Cysts In Amentioning
confidence: 99%